KEPUTUSAN PENUNDAAN KONSUMSI - Yuni Istanto (BALANCE: Economic, Business, Management and Accounting Journal, 2006)
Consumer engage in active decision time, which is time spent on    activities, and deciding where to purchase. Active decision time in consumer decisions and the extent of information search have been studied extensively. Thus is also important to study decision delay time in consumer decision making, which we define as the total elapsed time between need recognition and purchase. Decision delay time includes both active decision time and time the consumer spends on all other activities during the decision process.